Bogotá, a city in transition? Synergies between transitions to post-development and peacebuilding - GRANADA, Soledad (Utopía y Praxis Latinoamericana, 2023)
This work addresses the transitions to post-development in its synergistic dimension with peacebuilding in urban contexts, specifically in the city of Bogotá. A political ecology analysis is put forward around communitarian and territorial dimensions of transitions, with the purpose of recognizing the agencies of multiple actors and possible fugues to hegemonic development. From the perspective of environmental justice, we study the definitions of transition, we identify that these transitions are fundamentally characterized by three dimensions: (i) Human scale development, (ii) Community construction processes - social capital creation, (iii) Social representations about space and relationships with nature. We focus on general patterns that underlie inequalities, which constitute conflicting identities and lifestyles. We analyze in four examples, in border areas of the city, the factors associated with the nonviolent defense of the territory, and the emergency of community transition processes that contribute to the cultural transformation towards the pluriverse of cultures of peace.